Ocena pookluzivne reaktivne hiperemije pri bolnikih s hipotirozo - Gergar, Maša (Medicinski razgledi, 2013)
Backgrounds. Hypothyroidism is a condition in which dinkal, pathophysiological and biochemical changes are found due to thyriod hormone deficiency. Hypothyroidism is associated with an increased risk of cardiovascular diseases and an impairment of microvascular function before manifest dini cal signs. Our research aimed to detect potential changes in skin microvascular function in patients with hypothyroidism which may be indicative of endothelial dysfunction. We hypothesized that hypothyroidism causes alterations in skin microvascular reactivity due to a decrease in vasodilator capacity. Methods. Using laser Doppler flowmetry we measured skin blood flow in two representative measuring sites (volar aspect of the forearm and the finger pulp) in patients with hypothyroidism (N = 13) and healthy controls (N = 15). Skin microvascular reactivity was evaluated by inducing postocclusive reactive hyperemia obtained by a thr ee-minute ocdusion of the left brachial artery. Throughout the experiment, we measured skin temperature at the measuring sites. Simultaneously, a three-channel ECG was recorded, as well as systolic and diastolic blood pressure of aa. digitales in the fourth finger of the right hand using finapress device. Results. Baseline laser Doppler flowmetry, blood pressure of aa. digitales and heart rate were comparable between both groups. The duration of postocdusive reactive hyperemia at the finger pulp was significantly (p < 0.05) longer in the group of patiems. We also noticed a trend toward an increase in area under the postocclusive reactive hyperemia curve in patients. Conclusion. Results suggest that hypothyroidism induces hardly detectable functional changes in skin microcirculation, possibly due to altered endothelial function. Postocclusive reactive hyperemia parameters of patients indicate an increased vasodilator capacity comp ar ed to healthy subjects, which is in contrast with our hypothesis. Yet, our results speak in favour of isolated effects of elevated serum thyroid stimulating hormone.
Keywords: hipotiroza; hypozhyroidism; koža; skin microvascular system; endothelial function; mikrožilje kože; funkcija endotelija